The Effect Of International Trade And Investment On Indonesia's Economic - Maylani Patricia Tambun; Iga Mawarni Pohan; Khairani Alawiyah Matondang (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
The purpose of this study is to determine the effect of international trade and investment on Indonesia’s economic g International trade in this study is identical to net exports so it can be said that the more detailed goal is to Find out the effect of net exports and investment on Indonesia’s economic growth. The dependent variable in this study is Economic growth while the independent variables are net exports and investment. The method used in this research is the Library method. While the method of analysis uses the linear regression method using the Eviews application. The results of this study indicate that net exports (international trade) do not significantly influence economic growth. While Investment has a significant positive effect on economic growth.